Indústria cultural do entretenimento na escola: a sala de aula no parque de diversões do Hopi Hari - Lemos, José Roberto (2015)
This study aims to contribute to the discussion about the influence of today's technological devices, as well as the cultural entertainment industry by way of amusement parks, in this research, Hopi Hari and its educational laboratory (LEd), as "the ferret education" formal. It is in this complex relationship, which develop many variables, we try to penetrate to obtain information that could indicate how is the co-optation of students for the consumption of entertainment goods, and, through the cultural industry advertising, schools are invited to join these mechanisms disguised as culture, with the convincing element the idea that distraction learning occurs in a more efficient and enjoyable way. For both draw on a field of research that tried to investigate how this co-option in relation to students from a public school and a private of São Carlos, São Paulo State. Our analysis relied mainly on studies done by Critical Theory of Education and the ideas of his classic representatives as Adorno, Horkheimer, Benjamin and others, as well as their more contemporary representatives. The thematic approach was configured into four main chapters: the first sought to emphasize the origin of amusement parks, as well as the influence of the cultural products of the entertainment industry in the human experiences; in the second chapter we emphasize the relationship between the culture industry, schools and parks, highlighting the educational training offered by the Hopi Hari park for teachers in order to bring their students; the third was sought to understand how is the logic of fun as promoting public and private, and the consequences in the training process and the virtual explosion in concentrated distraction; the fourth chapter made the analysis of data obtained in field research as a subsidiary of our hypotheses regarding the concentrated distraction that occurs in the parks as opposed to attention and concentration as necessary requirement acquisition of knowledge.